2020
DOI: 10.1007/978-3-030-49461-2_14
|View full text |Cite
|
Sign up to set email alerts
|

Processing SPARQL Aggregate Queries with Web Preemption

Abstract: Executing aggregate queries on the web of data allows to compute useful statistics ranging from the number of properties per class in a dataset to the average life of famous scientists per country. However, processing aggregate queries on public SPARQL endpoints is challenging, mainly due to quotas enforcement that prevents queries to deliver complete results. Existing distributed query engines allow to go beyond quota limitations, but their data transfer and execution times are clearly prohibitive when proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…In a previous work [7], we demonstrated that a partial aggregation operator is preemptable. Computing partial aggregations on a preemptable server drastically reduces data transfer for most aggregate queries, while ensuring complete results.…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…In a previous work [7], we demonstrated that a partial aggregation operator is preemptable. Computing partial aggregations on a preemptable server drastically reduces data transfer for most aggregate queries, while ensuring complete results.…”
Section: Introductionmentioning
confidence: 85%
“…This extension allows estimating the result of a count-distinct query with a bounded error rate. -Additional experimental results that compare the performance of the extended operator and the previous operator [7]. Experimental results demonstrate that relying on estimates does not improve the execution time, but significantly reduces the data transfer for count-distinct queries, and in the general case, show that the proposed approach outperforms existing approaches used for processing aggregate queries.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations